Dreaming of a Self Beyond Whiteness and Isolation - John A. Powell (Washington University Journal of Law & Policy, 2005)
In this Essay I want to engage racial boundaries and social boundaries in general. I want to poke them, prod them, and examine how these boundaries are constructed—not only in the structures and arrangements of our society, but within our processes of self-identification. I want to look at how we create these boundaries, and how they, in turn, create us. I assert that these external boundaries and manifestations of whiteness and internal white identity are linked at a deep level and that a better understanding of this relationship helps to explain why whiteness and racial hierarchy are still reproduced across all of our spaces from the most public to a space as private as our dreams.
Keywords: Critical race theory; Race preferences (Affirmative action)